Inflammatory Biomarkers in Chronic Obstructive Pulmonary Disease - Comes Alexandra; Ianoşi Edith Simona; Jimborean Gabriela (Journal of Interdisciplinary Medicine, 2016)
Chronic obstructive lung disease (COPD) is a severe progressive disease associated with high morbidity and mortality. Early diagnosis and correct treatment improve the symptoms, quality of life and survival in COPD. Exacerbations of the disease are acute events that cause worsening of COPD symptoms (dyspnea, cough and/or sputum) and may require modification of stable COPD therapy. COPD exacerbations add inflammation, damage the quality of life, deteriorate the lung function, increase mortality and associate high socio-economic costs. Accurate early prediction of exacerbation and mortality risk facilitates patient selection upon risk, in order to provide appropriately targeted early treatment. The risk of having frequent exacerbations is clearly demonstrated by recognized studies in patients with specific criteria: previous exacerbation in the last year, decrease in FEV1s, increase in the score of St. George Questionnaire (life quality decline), high levels of several inflammatory biomarkers, such as neutrophils, C-reactive protein (CRP), fibrinogen, pro-calcitonin, eosinophils, IL-6, IL-8, chemokine ligand 18 (CCL-18/PARC), surfactant protein D (SP-D). Simultaneously elevated levels of CRP, fibrinogen and leukocyte count in COPD patients were associated with an increased risk for exacerbations. At the same time, elevated levels of the three biomarkers are associated with an increased risk of major comorbidities in COPD. Biomarker detection may be an additional tool for assessment and management of COPD comorbidities. Detection of pathologic levels of inflammatory biomarkers improves the ability to predict the risk mortality in COPD alongside with BODE index (BMI, obstruction in lung function, dyspnea scale, 6-minute walk test) and may provide a targeted treatment.